Profile of Social Arithmetic Problem Solving Ability of Grade VII Junior High School Students - Regina Afeanpah; Aloisius Loka Son; Eduardus B.S. Delvion (CV. Samuel Manurung and Co, 2023)
The aim of this study is to describe the profile of social arithmetic problem-solving abilities of Grade VII students in one of the junior high schools in the TTU Regency. The type of research used in this study is a qualitative description, and the subjects of the study were 17 students, of whom six were selected for interviews. The six students included two high-ability, two moderate-ability, and two low-ability students. The data analysis model used in this study is the interactive data analysis model developed by Miles and Huberman. The results of the study show that: 1) Students in the high-ability category were able to fulfill all indicators of problem-solving, including understanding the problem, devising a plan, carrying out the plan, and looking back; 2) Students in the moderate-ability category were able to meet the indicators of understand the problem, devising a plan, and carry out the plan, but were unable to meet the indicator of look back; 3) Students with low abilities were able to fulfill the steps of understanding the problem and devising a plan, but were unable to fulfill the steps of carrying out the plan and look back.